2010
DOI: 10.1111/j.1469-0691.2009.02917.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin disinfection with octenidine dihydrochloride for central venous catheter site care: a double-blind, randomized, controlled trial

Abstract: To compare the efficacy of two commercially available, alcohol-based antiseptic solutions for preparation and care of central venous catheter (CVC) insertion sites, with and without octenidine dihydrochloride, a double-blind, randomized, controlled trial was undertaken in the haematology units and in one surgical unit of two university hospitals. Adult patients with a non-tunnelled CVC were randomly assigned to two different skin disinfection regimens at the insertion site: 0.1% octenidine with 30% 1-propanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 35 publications
3
24
0
11
Order By: Relevance
“…While 10% aqueous povidone iodine alone is significantly less effective than alcohol-based products, the combination of povidone iodine with alcohol is only minutely less effective than alcohol combined with remanently acting compounds [6]. Similar findings have been demonstrated for other alcohol combinations with added remanent antiseptics, such as octenidine dihydrochloride [5]. …”
Section: The Impact Of Preoperative Skin Antisepsis On the Preventionsupporting
confidence: 63%
See 1 more Smart Citation
“…While 10% aqueous povidone iodine alone is significantly less effective than alcohol-based products, the combination of povidone iodine with alcohol is only minutely less effective than alcohol combined with remanently acting compounds [6]. Similar findings have been demonstrated for other alcohol combinations with added remanent antiseptics, such as octenidine dihydrochloride [5]. …”
Section: The Impact Of Preoperative Skin Antisepsis On the Preventionsupporting
confidence: 63%
“…Alcohol is commonly combined with compounds that have a remanent antimicrobial efficacy, such as chlorhexidine, because of the higher antiseptic efficacy [5] and, as a consequence, decreased incidence of SSI [6]. While 10% aqueous povidone iodine alone is significantly less effective than alcohol-based products, the combination of povidone iodine with alcohol is only minutely less effective than alcohol combined with remanently acting compounds [6].…”
Section: The Impact Of Preoperative Skin Antisepsis On the Preventionmentioning
confidence: 99%
“…Special focus should be given on proper hand hygiene and skin disinfection, as demonstrated in a recent randomized controlled trial which compared the efficacy of two commercially available, alcohol-based antiseptic solutions for preparation and care of CVC insertion sites, with and without octenidine dihydrochloride. It demonstrated that octenidine in alcoholic solution may be a better option than alcohol alone for the prevention of CVC-associated infections, due to significantly fewer positive cultures of the catheter tip and a non-significant reduction in catheter-associated bloodstream infections in the octenidine group [14]. Since all of our isolates were susceptible to TMP-SMX, this strengthens previous reports that show that TMP-SMX has the most potent in vitro activity against S. maltophilia and should probably be regarded as first line therapy [5,7].…”
Section: Discussionmentioning
confidence: 97%
“…However, octenidine has been shown to be at least equally potent as chlorhexidine concerning its antiseptic properties and it has been successfully used as an alternative to chlorhexidine for care of the insertion site in patients with central venous catheters. [14][15][16] Furthermore, daily bathing with octenidine resulted in a reduction in carriage rate of methicillinresistant S aureus (MRSA) in intensive care patients. 17 We primarily evaluated the effect of mupirocin nasal ointment and preoperative chlorhexidine/octenidine wash on SSI rates based on our standardized prospective surveillance protocol, adjusting for potential confounding factors in a quasiexperimental study.…”
mentioning
confidence: 99%